Contrasting effects of light and noise pollution interact with natural vegetation remnants: Human-related indicators of the habitat suitability for ungulates in the urban landscape - Michał Ciach; Hubert Faraś; Arkadiusz Fröhlich; Izabela Fedyń (Ecological Indicators, 2022)
The features of the urban landscape encouraging large ungulates expansion are not known. However, prevalence and abundance of wild boar Sus scrofa has been steadily increasing over the years, and nowadays the species has become a recognized component of urban wildlife in many parts of its range. The aim of this work was to select habitat and human-related factors that could affect the probability of the species occurrence and constitute the honest indicators of the habitat suitability for this ungulate in the urban landscape. The data on the presence of grubbed patches of ground (an honest indicator of occurrence) were collected on randomly selected sample plots (N = 100) within the city of Kraków (Poland). We found that wild boar used 45% of the sample plots. Whereas the occupied plots were spatially concentrated, the habitat variables increasing the probability of the species occurring in the urban landscape were the presence of large patches of woodland remnants and large areas of semi-natural meadows. However, the study also revealed a negative relationship between the presence of the species and artificial lighting but a positive one with anthropogenic noise pollution. Our results indicate that the urban landscape consists of surrogate habitats for this large mammal but light and noise pollution may have contrasting effects on the species’ occurrence. This indicates that the influence of human-related factors on the attractiveness of natural vegetation remnants for wildlife is more complex than merely a limiting factor. This reveals high potential of light and noise pollution as indicators of the habitat suitability for ungulates in the urban landscape.